Pengaruh dzikir dan doa terhadap penurunan nyeri pada pasien post sectio caesaria di RSU Islam Klaten - Isniawati Rohmiatun; Kamidah Kamidah (Journal of Health and Therapy, 2025)
Post-cesarean section pain is a common complaint that can hinder maternal recovery, including breastfeeding and newborn care. At RSU Islam Klaten, an average of 70 post-cesarean patients are treated each month. A spiritual, nonpharmacological approach using dhikr (remembrance) and prayer may increase relaxation and support endogenous analgesia through endorphins and serotonin. This study examined whether dhikr and prayer reduce pain intensity in post-cesarean patients. A pre-experimental, one-group pretest–posttest design was used. Sixty-two respondents were recruited through consecutive sampling. Guided dhikr and prayer were delivered for 30 minutes, and pain intensity was measured using the Numeric Rating Scale (NRS). Data were analyzed with the Wilcoxon test. Before the intervention, 41 respondents (66.1%) reported moderate pain and 21 (33.9%) reported severe pain. After the intervention, 29 (46.8%) reported mild pain, 32 (51.6%) moderate pain, and 1 (1.6%) severe pain. Wilcoxon results indicated a reduction in pain intensity following dhikr and prayer, suggesting this practice can be considered as an adjunct to standard postoperative care.